Individual Differences in Risky Decision Making: A Meta‐analysis of Sensation Seeking and Impulsivity with the Balloon Analogue Risk Task. (22nd April 2013) - Lauriola, Marco; Panno, Angelo; Levin, Irwin P.; Lejuez, Carl W.
SUMMARY To represent the state‐of‐the‐art in an effort to understand the relation between personality and risk taking, we selected a popular decision task with characteristics that parallel risk taking in the real world and two personality traits commonly believed to influence risk taking. A meta‐analysis is presented based on 22 studies of the Balloon Analogue Risk Task from which correlations with sensation seeking and impulsivity assessments could be obtained. Results calculated on a total of 2120 participants showed that effect size for the relation of sensation seeking with risk taking was in the small–moderate range (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t3ctk7w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />r¯</alternatives> = .14), whereas the effect size for impulsivity was just around the small effect size threshold (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t3ctk90" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />r¯</alternatives> = .10). Although we considered participants' demographics as moderators, we found only significantly larger effect sizes for the older adolescents and young adults compared with other ages. The findings of the present review supported the view that inconsistencies in personality–risk research were mostly due to random fluctuations of specific effect sizes, rather than to lack of theoretical ties or to measurement unreliability. It is also concluded that studies aimed at relating individual differences in personality to performance in experimental decision tasks need an appropriate sample size to achieve the power to produce significant results. Copyright © 2013 John Wiley & Sons, Ltd.